Predictors of Hospitals' Nonachievement of Baseline Nursing Standards for Pediatric Oncology. Issue 4 (July 2020) - Sullivan, Courtney E.; Morrissey, Lisa; Day, Sara W.; Chen, Yanjun; Shirey, Maria; Landier, Wendy
Abstract : Background: The International Society of Pediatric Oncology established baseline standards for pediatric oncology nursing; limited evidence is available to predict hospitals' capacity to meet these standards internationally. Objectives: The aims of this study were to (1) determine the proportion of hospitals that met, partially met or did not meet baseline standards for pediatric oncology nursing and (2) identify predictors of hospitals' nonachievement of baseline standards for pediatric oncology nursing. Methods/Analysis: A secondary analysis of International Society of Pediatric Oncology web-based survey data of baseline nursing standards was conducted. Predictor variables were derived from surveyed hospital characteristics and external data sources. Multivariable parsimonious logistic regression models identified predictors of hospitals' nonachievement of each standard. Results: Nurses from 101 hospitals across 54 countries completed the survey; 12% to 66% of hospitals reported meeting each of 6 baseline standards. Predictors of nonachievement of standards included low current health expenditure as percentage of gross domestic product, World Health Organization Region of Africa, United Nations "developing or transition" country classification, countries with fewer than 3 nurses/midwives per 1000 population, and hospitals without bone marrow transplant and/or intensive care units. Conclusions: Hospitals with characteristics predictive of inability to meet baseline standards will likely require greater capacity-building support and advocacy to improve the quality of nursing care. Implications for Practice: Findings from this study highlight internal and external factors that challenge the delivery of high-quality pediatric oncology nursing care internationally. Abstract : Supplemental digital content is available in the text.